Development of Arabic Language Curriculum Focused on Diversity and Inclusion - Muhammad Thohri (Universitas Islam Negeri Jurai Siwo Lampung, 2024)
This literature review explores the development of an Arabic language curriculum prioritizing diversity and inclusion in an interconnected global context. It aims to formulate a curriculum catering to learners from diverse cultural backgrounds, abilities, and learning preferences, ensuring fair access and meaningful engagement. The methodology involves an extensive literature review, expert consultations, and data collection through surveys, interviews, and focus group discussions. Thematic coding and triangulation facilitate data analysis, revealing the importance of integrating diverse perspectives and inclusive pedagogical approaches. The study emphasizes nurturing an inclusive learning environment that embraces differences and fosters mutual respect. It highlights implications for educators, curriculum developers, and policymakers, stressing deliberate efforts to address diversity and inclusion within Arabic language education. Inclusive practices can effectively address diverse learner needs, promote cross-cultural understanding, and cultivate belonging. This research advances inclusive language education and encourages further exploration in this critical field.